Crossing consciousness: a literature discussion exploring friends from the other side - López-Robertson, Julia (Colombian Applied Linguistics Journal, 2004)
This article will focus on the use of small group literature discussions as a curricular engagement that challenges children to think critically and to share the opinions they are forming about the books they read. This teacher research study took place in a bilingual second grade classroom and describes the discourse of four young bilingual children during a discussion about the book Friends From the Other Side/Amigos del otro lado (Anzaldúa, 1993). The question guiding the research is; how do young linguistically and socio economically diverse children make meaning from small group literature discussions about issues that relate to their lives?